Challenges in Testosterone Measurement, Data Interpretation, and Methodological Appraisal of Interventional Trials. Issue 7 (1st July 2016) - Trost, Landon W.; Mulhall, John P.
ABSTRACT: Introduction: Male hypogonadism is a common condition, with an increasing body of literature on diagnosis, implications, and management. Given the significant variability in testosterone (T) from a physiologic and assay perspective, a thorough understanding of factors affecting T values and study methodology is essential to interpret reported study outcomes appropriately. However, despite the large number of publications on T, there are no reference materials consolidating all relevant and potentially confounding factors necessary to interpret T studies appropriately. Aims: To create a resource document that reviews sources of T variability, free vs total T, assay techniques and questionnaires, and study methodology relevant to interpreting outcomes. Methods: A PubMed search was performed of all the T literature published on T variability, assay techniques, and T-specific questionnaires. Results were summarized in the context of their impact on interpreting T literature outcomes and methodology. Main Outcome Measures: Effect of various factors on T variability and their relevance to study methodology and outcomes. Results: Several factors affect measured T levels, including aging, circadian rhythms, geography, genetics, lifestyle choices, comorbid conditions, and intraindividual daily variability. The utility of free T over total T is debatable and must be compared using appropriate threshold levels. Among various assay techniques, mass spectrometry and equilibrium dialysis are gold standards. Calculated empirical estimates of free T also are commonly used and accepted. Hypogonadism-specific questionnaires have limited utility in screening for hypogonadism, and their role as objective end points for quantifying symptoms remains unclear. Numerous aspects of study methodology can directly or indirectly affect reported outcomes, including design (randomized, prospective, retrospective), duration, populations studied (age, comorbid conditions), low T threshold, therapeutic agent used, objective measurements and end points selected, and statistical interpretation. Conclusion: Critical appraisal of the T literature requires an understanding of numerous factors resulting in T variability, study design and methodology, and limitations of assay techniques and objective measurement scales.